APLIKASI SISTEM PENUAIAN AIR HUJAN (SPAH) DI KAWASAN PERUMAHAN - Shareh Musa, Sharifah Meryam; Md Yassin, Azlina; Wan Husin, Hanis; Shafii, Haryati (Journal of Techno-Social, 2018)
ABSTRACT Rain Water Harvesting System (RWH) is a best management method in effective water management practices in Malaysia. This system aims to slow down the flow of surface runoff and promote efficient use of water as an alternative water supply sources are free and safe to use. In addition, due to the water source that is not appreciated and waste water directly applicable without the community taking positive steps in the event that has occurred could deteriorate the water supply in Malaysia. In addition, the catchment area and destroyed because more land is used for construction of the illegal activity or lawful. This study was conducted to determine implementation and assess the effectiveness of rain water harvesting system. This study was conducted with qualitative methods by interviewing respondents from the developper, the council and contractor. The results of this study identify the design of a tank to suit the residential building, the total cost of installation is RM 3,000.00 per unit and the effectiveness of the RWH uses was carried by the housing developers are very satisfied with the system that has been built. With this, we can solve the water supply problems occur and contribute towards saving the treated water. Keywords: Rainwater Harvesting, Housing, Water Resourses, Water Resources Alternative